2008
DOI: 10.4314/jtdorl.v16i1.42056
|View full text |Cite
|
Sign up to set email alerts
|

Les Ethmoidites Aigues Exteriorisees De L\'enfant Etude De 11 Observations

Abstract: INTRODUCTION L'ethmoïdite aiguë (EA) est l'infection bactérienne des cellules du labyrinthe ethmoïdal. Il s'agit d'une infection sévère, nécessitant un diagnostic et un traitement urgents du fait du risque de complications ophtalmologiques et endocrâniennes [1].Elle survient le plus souvent entre l'âge de 6mois et 5 ans. Le signe d'appel est l'apparition dans un contexte fébrile d'un oedème palpébral [2]. Le traitement repose essentiellement sur l'antibiothérapie à large spectre. La chirurgie est réservée aux … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Several recent studies show that emergency ethmoid‐orbital and cerebral CT remain the examinations of choice for making the diagnosis and specifying the locoregional extension of the complications, allowing emergency treatment to be instituted. Our patient's clinical picture (high fever of 39.9°C, painful swelling, and protrusion of the left eye for several days the following nasopharyngitis) indicated this from the first day of hospitalization 7–12 . Inflammation with hyperleukocytosis remains an observation in several studies 6,13 .…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…Several recent studies show that emergency ethmoid‐orbital and cerebral CT remain the examinations of choice for making the diagnosis and specifying the locoregional extension of the complications, allowing emergency treatment to be instituted. Our patient's clinical picture (high fever of 39.9°C, painful swelling, and protrusion of the left eye for several days the following nasopharyngitis) indicated this from the first day of hospitalization 7–12 . Inflammation with hyperleukocytosis remains an observation in several studies 6,13 .…”
Section: Discussionmentioning
confidence: 57%
“…Orbital and subperiosteal abscesses, as well as orbital cellulitis, are the complications of ethmoidomaxillary sinusitis found by several authors, 2,6,17 but in this study, the medial frontal cerebral empyema and focal signs were found beyond the orbital cellulitis and the Chandler IV retro‐orbital abscess, and this would be explained by the indirect propagation of the infection by the hematogenous route through the ophthalmic veins without valves. In our study, blood culture before starting antibiotic therapy and the search for soluble antigens would have increased the probability of identifying the germ in our study 7,18 …”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Orbital and sub-periosteal abscesses, as well as orbital cellulitis, are the complications of ethmoidomaxillary sinusitis found by several authors [2,5,16], but in the present study, the medial frontal cerebral empyema and focal signs were found beyond the orbital cellulitis and the Chandler IV retro-orbital abscess, and this would be explained by the indirect propagation of the infection by the hematogenous route through the ophthalmic veins without valves. In our study, blood culture before starting antibiotic therapy and the search for soluble antigens would have increased the probability of identifying the germ in our study [6,17].…”
Section: Discussionmentioning
confidence: 93%